Efektivitas Peranan Kepala Desa Dalam Pembangunan Di Desa Massappa Kecamatan Sabbangparu Kabupaten Wajo - Muh. Hasbi Abbas; Burhanuddin Burhanuddin (Universitas 45 Surabaya, 2022)
This research discusses the effectiveness of the role of the Village Head in development in Massappa Village, Sabbangparu District, Wajo Regency. The effectiveness of the Village Head's function in implementing this development uses three effectiveness indicators, namely goal achievement, integration and adaptation. This research uses a quantitative research method. The data source in this research uses primary data sources with the data collection techniques used are observation, questionnaires and documentation. The results of the research show that the role of the Village Head in development is very effective. This can be seen from the achievement of goals where in implementing village development, most of the goals are achieved in accordance with the time specified, aspects of implementing development in Massappa Village do not require a long time because The Village Head has carried out 4 stages of development, and from the target aspect he has also achieved the previously determined targets and the community has felt the benefits. From the aspect of integration, the village head also always provides direction and makes agreements (consensus) for progress in development in the village, the village head also always coordinates with the hamlet head and also the community, then the form of adaptation carried out by the village head is that in every implementation the village head always adapts with the needs of the people of Massappa Village.